2003
DOI: 10.1016/s0020-7292(03)00341-2
|View full text |Cite
|
Sign up to set email alerts
|

High maternal hemoglobin and ferritin values as risk factors for gestational diabetes

Abstract: A number of studies have linked high maternal serum hemoglobin (Hb) levels in pregnancy with increased incidence of adverse pregnancy outcomes, such as low birth weight and small-forgestational-age newborns, pre-term births, increased perinatal mortality, and pre-eclampsia w1x. Lao et al. identified high maternal hemoglobin at the initial prenatal visit as a risk factor for gestational diabetes mellitus (GDM) w2x.This prospective study was conducted on 253 non-diabetic Turkish women with singleton pregnancies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 4 publications
1
43
1
Order By: Relevance
“…Hence, prospective studies that measure iron status well before GDM diagnosis are needed to establish temporality and to control for confounding by insulin resistance-mediated inflammation. Studies that have prospectively examined the association of ferritin with GDM risk have, however, been limited and inconsistent in their findings [8][9][10][11][12]. For instance, a study based in Lebanon found that high ferritin levels in early pregnancy were significantly associated with impaired glucose tolerance but not with GDM incidence, although the latter could be attributed to the small number of women with GDM in the study (n = 16) [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, prospective studies that measure iron status well before GDM diagnosis are needed to establish temporality and to control for confounding by insulin resistance-mediated inflammation. Studies that have prospectively examined the association of ferritin with GDM risk have, however, been limited and inconsistent in their findings [8][9][10][11][12]. For instance, a study based in Lebanon found that high ferritin levels in early pregnancy were significantly associated with impaired glucose tolerance but not with GDM incidence, although the latter could be attributed to the small number of women with GDM in the study (n = 16) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies investigating the association between iron status in pregnancy and the risk of GDM are few and inconsistent in their findings [8][9][10][11][12], and none have examined these associations with longitudinal measurements of iron status. In addition, the vast majority of the existing literature centres on serum ferritin as a biomarker of iron stores.…”
Section: Introductionmentioning
confidence: 99%
“…This change of weight may have a little influence on the gravidas in the 29 ∼ 32 week interval, but after the thirty-second week, the normal group's BMI can overtake the GDM group's. Inflammatory reaction factors, such as the WBC and the C-reaction protein (CRP), are significantly related with pregnancy insulin resistance and are causally related to one another [16,17]. Several studies have found that when the prenatal examination is conducted, the higher the HBG concentration, the more likely GDM is to develop [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin concentration was set to 13 gm% as per this study. 9 Previous history of hypertension, Diabetes Mellitus, renal disease, thyroid disorder, dyslipidemia, multiple pregnancy, previous history of pre-eclampsia, pregnant women with any other medication except for vitamins, Iron & Calcium, were excluded from the study. Height and weight of the individuals were measured.…”
Section: Methodsmentioning
confidence: 99%
“…8 Some studies have linked high maternal serum hemoglobin levels (Hb = 13.2 gm%) in pregnancy outcomes, such as preeclampsia, preterm birth and small for gestational age. 9 Many investigators believe that the conditions for the development of preeclampsia are set as early as the first trimester. 10 Present study is done to know the relationship between high maternal haemoglobin and PIH .…”
Section: Introductionmentioning
confidence: 99%